1998
DOI: 10.1007/s002130050618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delivery rate and non-contingent infusion of cocaine on cocaine self-administration in rhesus monkeys

Abstract: The goal of this study was to determine whether slowly infused, response-independent cocaine would reduce cocaine self-administration in an animal model of drug abuse. Seven male rhesus monkeys self-administered i.v. cocaine on a fixed-ratio 30 schedule (5-min time-out). With unit dose (0.056 mg/kg per infusion for one monkey and 0.032 mg/kg per infusion for the rest) and infusion volume (0.5 ml) held constant, the rate of delivery was manipulated (0.125, 0.1875, 0.375, 0.75 and 3 ml/min, with infusions lastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 17 publications
8
55
0
Order By: Relevance
“…Rather, these findings suggest that cocaine produced a nonselective decrease in the ability of the monkeys to perform the key-press responses or a nonselective decrease in the reinforcing effects of both cocaine and food. In agreement with this conclusion, previous studies that examined cocaine-and food-maintained responding independently also found that acute, noncontingent cocaine decreased high-dose cocaine selfadministration only at doses that also decreased foodmaintained responding (Glowa and Fantegrossi, 1997;Panlilio et al, 1998).…”
Section: Effects Of Environmental Manipulations On Cocaine Vs Food Chsupporting
confidence: 81%
“…Rather, these findings suggest that cocaine produced a nonselective decrease in the ability of the monkeys to perform the key-press responses or a nonselective decrease in the reinforcing effects of both cocaine and food. In agreement with this conclusion, previous studies that examined cocaine-and food-maintained responding independently also found that acute, noncontingent cocaine decreased high-dose cocaine selfadministration only at doses that also decreased foodmaintained responding (Glowa and Fantegrossi, 1997;Panlilio et al, 1998).…”
Section: Effects Of Environmental Manipulations On Cocaine Vs Food Chsupporting
confidence: 81%
“…These data suggest that the rate of onset may play an important role in the reinforcing strength of psychomotor stimulants. Consistent with the latter interpretation, when cocaine was infused more slowly, it was found to be less effective as a reinforcer in nonhuman primates (Panlilio et al, 1998). Similarly, the cocaine analog HD-23, which takes 60 min to attain significant binding was not as reinforcing in rhesus monkeys as were cocaine or methylphenidate (Lile et al, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…oral) resulting in slower drug uptake (Volkow et al, 2000). When cocaine was infused more slowly, it was found to be less effective as a reinforcer in nonhuman primates (Balster and Schuster, 1973;Panlilio et al, 1998). Similarly, the cocaine analog HD-23, which takes 60 min to attain significant binding was not as reinforcing in rhesus monkeys as were cocaine or methylphenidate (Lile et al, 2003).…”
Section: Discussionmentioning
confidence: 99%